The Lightless Sky : An Afghan Refugee Boy's Journey of Escape to a New Life in Britain - Passarlay, Gulwali; Ghouri, Nadene (London Atlantic Books, 2015)
'To risk my life had to mean something. Otherwise what was it all for?' Gulwali Passarlay was sent away from Afghanistan at the age of twelve, after his father was killed in a gun battle with the US army for hiding Taliban fighters. Smuggled into Iran, Gulwali began a twelve month odyssey across Europe, spending time in prisons, suffering hunger, cruelty, brutality, nearly drowning in a tiny boat on the Mediterranean. Somehow he survived, and made it to Britain, no longer an innocent child but still a boy of twelve. Here in Britain he was fostered, sent to a good school, won a place at a top university, and was chosen to carry the Olympic torch in 2012. He wants to tell his story - to bring to life the plight of the thousands of men, women and children who risk their lives to leave behind the troubles of their homelands. Many die along the way, some are sent back to face imprisonment and possible death, some survive and make it here, to a country which offers them the chance of a life of freedom and opportunity. One boy's story is the central story of our times, and this memoir celebrates the triumph of courage and determination over adversity.
Include Map and Color Illustrations.
English Biography.
Keywords: Refugees -- Great Britain -- Afghanistan -- Afghans